Perancangan Dan Implementasi Sistem Penunjang Keputusan Penilaian Kinerja Dosen Di Universitas Muhammadiyah Jambi Menggunakan Metode Topsis - Etriyanti, Siska; Jasmir; Benni Purnama (LPPM Universitas Dinamika Bangsa, 2025)
Faculty performance assessment is a crucial factor in maintaining and improving academic quality in higher education institutions, including Universitas Muhammadiyah Jambi. However, the current evaluation methods are still subjective and manual, making them susceptible to bias and inefficiency. Therefore, this study aims to design and implement a Decision Support System for faculty performance evaluation using the TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) method. This method allows faculty ranking based on predefined criteria, such as teaching, research, community service, and other supporting elements. The system is designed to make the evaluation process more objective, transparent, and efficient. Implementation results indicate that the developed system can reduce subjectivity in assessments, enhance decision-making accuracy, and accelerate the faculty performance evaluation process. Thus, this system is expected to be an innovative solution for Universitas Muhammadiyah Jambi in improving academic quality and supporting faculty professional development. Keywords: Faculty performance evaluation, Decision Support System, TOPSIS, Universitas Muhammadiyah Jambi